Analisis Faktor-faktor yang Memengaruhi Pertumbuhan Aset Bank Syariah di Indonesia - Aini, Mega Pratitis Nur (Journal of Economics and Social Sciences (JESS), 2022)
This study aims to analyze the effect of bank internal variables (NPF, ROA, FDR, CAR, and BOPO) as well as bank external variables (inflation) on the growth of Islamic bank assets in Indonesia from 2009-2019. This type of research is quantitative and the data analysis technique uses multiple linear regression from 2009 to 2009. The results showed that simultaneously the variables NPF, ROA, CAR, FDR, BOPO, and inflation had a significant effect on the growth of Islamic banking assets in Indonesia in the 2009-2019 period. Partially the variables NPF, FDR, and BOPO have a negative and significant effect on the growth of Islamic banking assets in Indonesia in the 2009-2019 period. The CAR variable has a significant positive effect on the growth of Islamic banking assets in Indonesia in the 2009-2019 period. In addition, the ROA and inflation variables have no effect on the growth of Islamic banking assets in Indonesia for the 2009-2019 period. The BOPO variable is the variable that has the most influence on the growth of Islamic banking assets in Indonesia for the 2009-2019 period, so to increase asset growth the bank is required to maintain the BOPO value properly. Penelitian ini bertujuan menganalisis pengaruh variabel internal bank (NPF, ROA, FDR, CAR dan BOPO) serta variabel ekstrernal bank (inflasi) terhadap pertumbuhan aset bank syariah di Indonesia tahun 2009-2019. Jenis penelitian adalah kuantitaif dan Teknik analisis data mengunakan regresi linier berganda dari tahun 2009 sampai tahun. Hasil penelitian menunjukkan bahwa secara simultan variabel NPF, ROA, CAR, FDR, BOPO, Inflasi berpengaruh signifikan terhadap pertumbuhan aset perbankan syariah di Indonesia periode 2009-2019. Secara parsial variabel NPF, FDR, BOPO berpengaruh negatif dan signifikan terhadap pertumbuhan aset perbankan syariah di Indonesia periode 2009-2019. Variabel CAR berpengaruh positif signifikan terhadap pertumbuhan aset perbankan syariah di Indonesia periode 2009-2019. Selain itu variabel ROA dan Inflasi tidak berpengaruh terhadap pertumbuhan aset perbankan syariah di Indonesia periode 2009-2019. Variabel BOPO merupakan variabel yang paling berpengaruh terhadap pertumbuhan aset perbankan syariah di Indonesia periode 2009-2019, maka untuk meningkatkan pertumbuhan aset pihak bank wajib menjaga nilai BOPO dengan baik.